CLINICoSCope -A Prospective Observational Study in India on “Clinic on Some Common Orthopedic Pregnancy Related Problems Explored” - Agarwal, Sharat; Agarwal, Manika; Rema Arengh, Rimse; Rajkonwar, Jitumoni (International Journal of Nursing Research, 2023)
Introduction: The biomechanical, hormonal, and vascular changes that are induced by pregnancy results in variety of musculoskeletal problems. It has been found that majority of women during pregnancy experience temporary disabilities. The assessment was done to observe the impact of age, parity, and body mass index (BMI) of the pregnant ladies on the bone and muscular symptoms experienced during pregnancy. Aim of the Study: It was to find out the data on orthopedic problems in pregnant ladies. Materials and Methods: Hundred patients attending obstetrics and gynecology outpatient department after 30 weeks of gestation were subjected to a pre-structured questionnaire regarding bone and joint or muscle pain during pregnancy. The variables in the patient population under study were parity, age, and BMI. All the data were compiled and statistical analysis was done. Results and Observations: Data were analyzed using analysis tool pack visual basic for application in Excel. A positive correlation between age, BMI >25, and parity was found with regard to orthopedic problems. Lower back pain was found to be the most frequent complaint across all age groups. The study also suggests that overweight pregnant women, high order parity women are risk factor for musculoskeletal problems such as low back pain, tingling, pain in leg, calf swelling, paraesthesia, pubic pain, knee pain, pain in back, pelvic pain, pain in arm, and pain in groin. Conclusion: This study would create awareness regarding bone and muscle disorders in pregnancy leading to timely diagnosis and management.